Consulting project for the lubricants exports division at GALP Energia assessing the attractiveness of the Latin American lubricants market in the context of a potential partnership with Latina - Carlota Collares Pereira, Carlota Collares (2021)
The following report seeks to assess the attractiveness of the Latin American lubricants market in the context of a potential partnership with Latina1. Galp Energia, a Portuguese Oil and Gas company, presented the project to NOVA SBE’s Management Consulting Lab initiative, which, in turn, had allocated the project to a team of four students with complementary academic backgrounds. With Galp’s Exports Division support, the main goal was to assess the economic and financial viability of entering the Latin American market with a local partner. For that purpose a market assessment was conducted, followed by a financial analysis of the two-staged partnership and lastly, the team provided Galp with valuable recommendations on how to pursue the internationalization strategy and approach the Latin American partner.